Medium chain triglyceride and medium-and long chain triglyceride: metabolism, production, health impacts and its applications – a review - Yee, Ying Lee; Teck, Kim Tang; Eng, Seng Chan; Eng, Tong Phuah; Oi, Ming Lai; Chin, Ping Tan; Ab Karim, Nur Azwani; Mat Dian, Noor Lida Habi; Joo, Shun Tan (Taylor and Francis, 2022)
Structured lipid is a type of modified form of lipid that is “fabricated” with the purpose to improve the nutritional and functional properties of conventional fats and oils derived from animal and plant sources. Such healthier choice of lipid received escalating attention from the public for its capability to manage the rising prevalence of metabolic syndrome. Of which, medium-chain triacylglycerol (MCT) and medium-and long-chain triacylglycerol (MLCT) are the few examples of the “new generation” custom-made healthful lipids which are mainly composed of medium chain fatty acid (MCFA). MCT is made up exclusively of MCFA whereas MLCT contains a mixture of MCFA and long chain fatty acid (LCFA), respectively. Attributed by the unique metabolism of MCFA which is rapidly metabolized by the body, MCFA and MCT showed to acquire multiple physiological and functional properties in managing and reversing certain health disorders. Several chemically or enzymatically oils and fats modification processes catalyzed by a biological or chemical catalyst such as acidolysis, interesterification and esterification are adopted to synthesis MCT and MLCT. With their purported health benefits, MCT and MLCT are widely being used as nutraceutical in food and pharmaceutical sectors. This article aims to provide a comprehensive review on MCT and MLCT, with an emphasis on the basic understanding of its structures, properties, unique metabolism; the current status of the touted health benefits; latest routes of production; its up-to-date applications in the different food systems; relevant patents filed and its drawbacks.